Repositioning of Control of Objects by Creditors in the Execution Process According to Law Number 42 of 1999 concerning Fiduciary Guarantees - Riza Puspita Sari; Rika Puspita Sari (Yayasan Insan Mulia Bima, 2025)
This study examines consumer protection against online transaction crimes in accordance with Law The purpose of this study is to analyze and describe the execution of the control of fiduciary collateral objects for creditors according to Law Number 42 of 1999 concerning fiduciary collateral and to analyze and describe the obstacles and solutions to the execution of fiduciary collateral against defaulting debtors. This research method uses an empirical legal research method with a statutory and case approach. The legal materials used in this study are primary legal materials, namely the Civil Code and Law No. 42 of 1999 concerning Fiduciary Collateral and secondary legal materials. The results of this study are: The process of executing fiduciary collateral must follow the established legal procedures, namely through an agreement between the creditor and the debtor regarding breach of promise, or through a valid court decision. The process of executing fiduciary collateral consists of four stages, namely: 1) the initial monitoring stage, namely the classification of debtors based on the potential for bad debt; 2) the warning stage, namely at this stage the creditor delivers a warning of late payment and sanctions to the debtor; 3) warning letter issuance stage, namely the creditor verifies and issues a warning letter to the debtor who is experiencing bad credit; 4) execution stage, namely the execution carried out by the creditor after the debtor receives the third warning letter. Constitutional Court Decision Number 18/PUU-XVII/2019 has provided a legal interpretation that the executorial power of the Fiduciary Guarantee Certificate cannot be enforced immediately, but is dependent on certain circumstances, for example: a default agreement by the creditor and debtor or the debtor's willingness to hand over the fiduciary guarantee object. Obstacles and solutions in the execution of fiduciary guarantees include: 1) the collateral object is not in the hands of the debtor when the execution is carried out, the solution involves debtor education, digitization of records, firm legal action, and increased supervision; 2) the obstacle of intervention by mass organizations/NGOs, the solution is to increase legal understanding, mediation, law enforcement, transparency, and focus on appropriate roles; 3) the obstacle of the fiduciary object being in the TNI/POLRI/Lawyer/Judge environment, the solution is a legal approach through the courts, coordination, mediation, and compliance with legal procedures.